Guideline adherence and survival of patients with candidaemia in Europe: results from the ECMM Candida III multinational European observational cohort study - SİLİ, ULUHAN (My University, 2023)
Background: The European Confederation of Medical Mycology (ECMM) collected data on epidemiology, risk factors, treatment, and outcomes of patients with culture-proven candidaemia across Europe to assess how adherence to guideline recommendations is associated with outcomes. Methods: In this observational cohort study, 64 participating hospitals located in 20 European countries, with the number of eligible hospitals per country determined by population size, included the first ten consecutive adults with culture-proven candidaemia after July 1, 2018, and entered data into the ECMM Candida Registry (FungiScope CandiReg). We assessed ECMM Quality of Clinical Candidaemia Management (EQUAL Candida) scores reflecting adherence to recommendations of the European Society of Clinical Microbiology and Infectious Diseases and the Infectious Diseases Society of America guidelines. Findings: 632 patients with candidaemia were included from 64 institutions. Overall 90-day mortality was 43% (265/617), and increasing age, intensive care unit admission, point increases in the Charlson comorbidity index score, and Candida tropicalis as causative pathogen were independent baseline predictors of mortality in Cox regression analysis. EQUAL Candida score remained an independent predictor of mortality in the multivariable Cox regression analyses after adjusting for the baseline predictors, even after restricting the analysis to patients who survived for more than 7 days after diagnosis (adjusted hazard ratio 1·08 [95% CI 1·04–1·11; p<0·0001] in patients with a central venous catheter and 1·09 [1·05–1·13; p<0·0001] in those without one, per one score point decrease). Median duration of hospital stay was 15 days (IQR 4–30) after diagnosis of candidaemia and was extended specifically for completion of parenteral therapy in 100 (16%) of 621 patients. Initial echinocandin treatment was associated with lower overall mortality and longer duration of hospital stay among survivors than treatment with other antifungals. Interpretation: Although overall mortality in patients with candidaemia was high, our study indicates that adherence to clinical guideline recommendations, reflected by higher EQUAL Candida scores, might increase survival. New antifungals, with similar activity as current echinocandins but with longer half-lives or oral bioavailability, are needed to reduce duration of hospital stay. Funding: Scynexis.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; BULAŞICI HASTALIKLAR; Life Sciences (LIFE); IMMUNOLOGY; INFECTIOUS DISEASES; Bulaşıcı hastalıklar; Sağlık Bilimleri; Infectious Diseases; Health Sciences